Method for preparing catalyst with piezoelectric property from copper slag and application
Through the catalyst BSFM synthesized by copper slag and Bi2O3, the by-product pollution and cost of arsenic and organic wastewater treatment in the prior art was solved, and the effect of efficient degradation of antibiotics and arsenic was achieved, and the application prospects in the field of environmental catalysis were demonstrated. .
Patent Information
- Application Number
- CN202411272755.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-11
AI Technical Summary
When treating wastewater contaminated by arsenic and organic matter, the prior art has problems such as by-product pollution, high cost and long treatment cycle. The bismuth-based composite oxide has a low conduction band level in photocatalytic aspects, which limits its application.
The catalyst BSFM with piezoelectric properties was prepared by synthesis of copper slag and Bi2O3. The specific surface area and reactive sites of the catalyst were increased by calcining and hydrothermal synthesis, and MnO2 was used to support the catalyst surface to improve charge mobility and catalytic activity.
The prepared catalyst BSFM has a high specific surface area, many reactive sites, and stable structure. It can effectively degrade antibiotics and arsenic, significantly improve catalytic efficiency, simple process and low cost, and is suitable for industrial applications.
Smart Images

Figure CN119158589A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary utilization of solid wastes, and specifically relates to a method for preparing a catalyst with piezoelectric properties by utilizing copper slag and an application of the catalyst in removing organic matter and arsenic. Background Art
[0002] Arsenic (As) is a highly toxic metalloid element widely distributed in the environment. The irrigation of arsenic-containing groundwater and the use of arsenic-containing pesticides have caused serious soil pollution. As can cause serious health effects, including lung cancer, bladder cancer and kidney cancer, as well as many neurological, renal, blood and respiratory diseases. Arsenic exists mainly in the form of As(III) and As(V) in nature. As(III) exhibits stronger toxicity, solubility and mobility than As(V). The typical background concentration of arsenic in soil does not exceed 100 mg / kg, and in fresh water does not exceed 10 μg / L. At present, the following three types of tetracycline antibiotics are common: chlortetracycline (CTC), oxytetracycline (OTC), tetracycline (TC), etc. These antibiotics are widely used in livestock and poultry farming and aquaculture. Because they cannot be completely absorbed and metabolized by the animal body, about 40% to 90% are eventually excreted from the body into the environment in the form of original drugs or isomers with livestock and poultry feces and urine, affecting the environment and human health and safety. The combined pollution of arsenic and organic matter not only occurs in the water environment, but is also common in the soil. Due to the promotion of organic fertilizers and widespread arsenic pollution, antibiotic-contaminated feces may be applied to arsenic-contaminated soil, leading to the combined pollution of arsenic and antibiotics in the soil. The coexistence of arsenic and TCs is very common, especially in agricultural soils.
[0003] The removal technologies that have been developed for arsenic and organic pollution include: adsorption, chemical precipitation, oxidation, ion exchange, photocatalysis, etc. The most obvious feature of the advanced oxidation process is that it can produce hydroxyl radicals OH after oxidation reaction with oxidants. Due to the high activity of hydroxyl radicals, they will undergo oxidative decomposition reactions with organic pollutants in wastewater, degrading pollutants into carbon dioxide and water, which can achieve the effect of degrading pollutants. Various oxidation processes such as chemical oxidants (chlorine, permanganate, etc.) and advanced oxidation processes (AOPs) (such as UV / H2O2, Fenton reaction, UV / nitrite, UV / hydrogen persulfate) are widely used in As(III) pre-oxidation or oxidative degradation of organic matter. However, conventional chemical oxidants (chlorine, chloramines and ozone) may produce toxic byproducts such as trihalomethanes, nitrosamines and bromates; the Fenton process is highly dependent on pH and is prone to sludge; the long treatment cycle and high cost of ultraviolet light treatment limit its practical application. The emerging piezoelectric catalytic effect has attracted great attention. When external strain is applied to a piezoelectric material, a polarization electric field appears on the surface of the piezoelectric material, causing the centers of positive and negative charges to shift. This internal piezoelectric potential maintained with stress can induce the separation of piezoelectrically generated electron-hole pairs and trigger redox reactions.
[0004] Bi-based composite oxides have attracted much attention due to their excellent photooxidation ability and efficient photocatalytic degradation of organic pollutants and water oxidation performance. However, the relatively low conduction band level limits their further application in photocatalytic hydrogen evolution and the overall water splitting process. 25 FeO 40 Bismuth is a bismuth-based semiconductor material that responds to visible light. It has a narrow band gap and exhibits excellent electrical, magnetic and light absorption properties, which makes it have great application potential in the fields of multiferroic materials and photocatalytic materials. However, it has a high recombination rate of photogenerated electrons and holes, which affects the catalytic performance and practical application of the catalyst. 12 SiO 20 It has good carrier mobility, narrow band gap, excellent photoelectric, acousto-optical and dielectric properties, and should be an ideal photocatalytic material. However, the synthesized Bi 12 SiO 20 The particle size is always at the micrometer level, resulting in a very small specific surface area, which greatly restricts the photocatalytic performance.
[0005] Copper slag is solid waste formed during the smelting of copper alloys. It is mainly composed of Fe2O3, SiO2, Al2O3, CaO, etc. The overall utilization rate of copper slag is low, and most of it is still stored, occupying a large amount of land and causing environmental pollution. Copper slag contains a large amount of ferrous silicate, which has gelling properties after alkali activation. In addition, copper slag also contains a large amount of magnetite. The prepared product has magnetic properties, which is convenient for adsorbent separation and recovery. Summary of the invention
[0006] The present invention provides a method for preparing a catalyst with piezoelectric properties by using copper slag. The catalyst prepared by the present invention has high specific surface area, many reaction active sites, good piezoelectric properties, high metal atom utilization rate, stable structure, and has good application value and prospect. The method of the present invention has simple process, convenient operation, easy to obtain raw materials, low cost and high yield.
[0007] The method for preparing a catalyst having piezoelectric properties by using copper slag in the present invention is as follows:
[0008] 1. Dry the copper slag at a constant temperature of 60°C for 36-48 hours, ball-mill for 2-3 hours, and sieve through a 180-mesh sieve to obtain copper slag powder. Place the copper slag powder in a crucible and place it in a muffle furnace at 450-550°C for 3 hours, and grind it into copper slag powder;
[0009] 2. Grind the calcined copper slag powder, Bi2O3 and anhydrous ethanol in a mortar for 0.5-1h, the mass ratio of calcined copper slag to Bi2O3 is 1:0.3-2, pour the mixture into a nickel crucible, place the nickel crucible in a muffle furnace and roast at 550-650°C for 1h;
[0010] 3. Mix manganese sulfate monohydrate, the calcined product in step 2 and water to obtain a mixed solution, add potassium permanganate solution dropwise to the mixed solution, and finally heat in a water bath at 45-55° C. for 12 hours. The reaction product is separated into solid and liquid, and the solid is washed, dried and ground to obtain a catalyst BSFM with piezoelectric properties, wherein the mass ratio of the calcined product to manganese sulfate monohydrate is 1.7-8.5:1, and the mass ratio of the calcined product to potassium permanganate is 2.7-14:1.
[0011] Another object of the present invention is to use the catalyst prepared by the above method in catalytic degradation of antibiotics and arsenic.
[0012] Compared with the prior art, the present invention has the following advantages:
[0013] (1) The present invention uses industrial solid waste copper slag as raw material, and after a simple roasting treatment, solid phase synthesis with Bi2O3 is used to prepare the catalyst carrier; although the solid phase reaction method may cause agglomeration between powder particles and the generation of impurities during the high temperature heat treatment process, it has the advantages of simple process and low cost, and is the main method most likely to obtain industrial application;
[0014] (2) The present invention adopts a simple hydrothermal synthesis to successfully load amorphous MnO2 on the surface of the catalyst carrier, and prepares a catalyst BSFM with the advantages of high specific surface area, multiple reaction active sites, good piezoelectric performance, high metal atom utilization rate, stable structure, etc.; and the preparation method is simple to operate, has a high yield, can significantly increase the specific surface area of the catalyst, and improve the catalytic efficiency of the catalyst; a heterojunction is constructed between the carrier and MnO2, and the charge mobility is successfully improved. While MnO2 plays a role, it provides high surface defects and uniform catalytic active sites; at the same time, the preparation method of the present invention also has the advantages of simple process, convenient operation, easy availability of raw materials, low cost, easy to realize industrial production, and has great application prospects, especially in the field of environmental catalysis;
[0015] (3) The catalyst BSFM prepared by the present invention is mixed with tetracycline hydrochloride wastewater and stirred, and the organic pollutants can be effectively degraded under constant temperature oscillation or ultrasonic conditions, which has the advantages of simple process, convenient operation, low cost, high treatment efficiency, and good degradation effect. Moreover, when uniformly mixed with wastewater containing the highly toxic element As(III), the toxic element As(III) can be catalytically oxidized into less toxic As(V). The catalyst BSFM oxidizes and adsorbs As(III) and As(V) under constant temperature oscillation or ultrasonic conditions, effectively reducing the toxicity of the wastewater. It has good degradation and adsorption effects for treating wastewater containing organic matter and arsenic in life, and has good development prospects in the field of treating highly toxic organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The XRD patterns of the products at different stages of the catalyst preparation process in Example 1 and the amorphous manganese dioxide catalyst in Comparative Example 4;
[0017] Figure 2 is the SEM image of the catalyst support BSFO;
[0018] Figure 3 is the SEM image of catalyst BSFM;
[0019] Figure 4 XRD patterns of bismuth silicate catalyst BSO (pure), bismuth ferrite catalyst BFO (pure), bismuth silicate and bismuth ferrite composite catalyst BSFO (pure), catalyst carrier BSFO of Example 1, and catalyst BSFM of Example 1;
[0020] Figure 5 is the SEM image of the amorphous manganese dioxide catalyst;
[0021] Figure 6 It is a time-degradation efficiency diagram when the catalyst in Example 1 and Comparative Examples 1-4 degrades tetracycline hydrochloride solution under oscillation conditions;
[0022] Figure 7 It is a time-degradation efficiency diagram when the catalyst in Example 1 and Comparative Examples 1-4 degrades tetracycline hydrochloride solution under ultrasonic conditions;
[0023] Figure 8 It is a fitting diagram of the degradation rate constant when the catalyst in Example 1 and Comparative Examples 1-4 degrades tetracycline hydrochloride solution under ultrasonic conditions;
[0024] Fig. 9 It is a time-degradation efficiency diagram of the catalysts in Example 1 and Comparative Examples 1-4 when degrading As(III) under oscillation conditions;
[0025] Fig.10 It is a time-degradation efficiency diagram of the catalysts in Example 1 and Comparative Examples 1-4 when degrading As(III) under ultrasonic conditions;
[0026] Fig.11 It is a fitting diagram of the degradation rate constant when the catalysts in Example 1 and Comparative Examples 1-4 degrade As(III) under ultrasonic conditions. DETAILED DESCRIPTION
[0027] The content of the present invention is further explained by the following examples, but these examples do not limit the protection scope of the present invention. The methods in the embodiments are conventional methods unless otherwise specified, and the reagents used are conventional reagents sold on the market unless otherwise specified;
[0028] The copper slag used in the following examples mainly contains Fe2O3 73.79%, SiO2 10.47%, Al2O3 1.32%, CaO 3.02%, and ZnO 3.78%;
[0029] Example 1: Preparation of a catalyst with piezoelectric properties using copper slag
[0030] 1. Dry the copper slag at 60℃ for 40h, ball-mill for 2h and sieve through 180 mesh to obtain copper slag powder. Place the copper slag powder in a crucible and calcine it in a muffle furnace at 500℃ for 3h. Grind to obtain dark reddish brown copper slag powder. The XRD pattern of the calcined copper slag is shown in Figure 1 From the figure, it can be seen that the main characteristic peaks of the crystal phase materials are Fe2O3 and SiO2, and the characteristic peaks of Fe2O3 appear around 2θ=25°~45° and 2θ=50°~60°, indicating that CS contains a large amount of Fe2O3;
[0031] 2. Put 1.4g of calcined copper slag powder and 1.165g of Bi2O3 into a mortar, add anhydrous ethanol and grind for 0.5 hours to obtain a uniform mixed powder, put it into a nickel crucible, and place it in a muffle furnace for roasting at 600°C for 1 hour. After natural cooling, grind it with a mortar to obtain a catalyst carrier BSFO. The SEM image of the catalyst carrier BSFO is shown in Figure 2 ,It can be seen from the figure that the catalyst carrier has a block and sheet structure;
[0032] 3. Take 0.14g of manganese sulfate monohydrate and 0.3g of catalyst carrier, dissolve them in 50mL of deionized water, record it as solution A, take 0.086g of potassium permanganate and dissolve it in 50mL of deionized water to prepare potassium permanganate solution, add the potassium permanganate solution dropwise into solution A and mix well; put the mixed solution into a constant temperature water bath heating pot, keep it warm at 50℃ for 12h, filter it after natural cooling, rinse the solid with water 5 times, dry it at 60℃ for 12h, grind it with a mortar to obtain catalyst BSFM, the SEM image of catalyst BSFM is shown in Figure 3 ,It can be seen from the figure that MnO2 is uniformly loaded on the catalyst carrier and forms a layered cross-linked network structure;
[0033] The XRD patterns of the catalyst support BSFO and the catalyst BSFM are shown in Figure 1 From the figure, it can be seen that both the catalyst carrier BSFO and the catalyst BSFM have strong Bi 25 FeO 40 (JCPDSNo.46-0416) and Bi 12 SiO 20 ((JCPDS No.37-0485) diffraction peaks, indicating that the product contains both bismuth silicate and bismuth ferrite.
[0034] Example 2: The method of this example is the same as that of Example 1, except that 0.035 g of manganese sulfate monohydrate and 0.3 g of the catalyst carrier are dissolved in deionized water, and 0.0215 g of potassium permanganate is dissolved in 50 mL of deionized water.
[0035] Example 3: The method of this example is the same as that of Example 1, except that 0.07 g of manganese sulfate monohydrate and 0.3 g of the catalyst carrier are dissolved in deionized water, and 0.043 g of potassium permanganate is dissolved in 50 mL of deionized water.
[0036] Example 4: The method of this example is the same as that of Example 1, except that 0.105 g of manganese sulfate monohydrate and 0.3 g of the catalyst carrier are dissolved in deionized water, and 0.0645 g of potassium permanganate is dissolved in 50 mL of deionized water.
[0037] Example 5: The method of this example is the same as that of Example 1, except that 0.578 g of manganese sulfate monohydrate and 1 g of the catalyst carrier are dissolved in deionized water, and 0.36 g of potassium permanganate is dissolved in 50 mL of deionized water.
[0038] Comparative Example 1: Preparation of bismuth silicate catalyst
[0039] 0.8 g of silicon dioxide and 2.33 g of bismuth oxide were taken, put into a mortar, added with anhydrous ethanol and ground for 0.5 hours to obtain a uniform mixed powder, put into a nickel crucible, placed in a muffle furnace at 600 ° C for 1 hour, and after natural cooling, ground with a mortar to obtain a bismuth silicate catalyst BSO (pure), and its XRD pattern is shown in Figure 4 From the figure, we can see that 24.82°, 27.88°, 30.53°, 33.10°, 52.67°, 55.97° and 62.24° correspond to the (220), (310), (222), (321), (530), (611) and (631) planes of BSO (pure), respectively, indicating that pure bismuth silicate Bi 12 SiO 20 Successfully synthesized.
[0040] Comparative Example 2: Preparation of bismuth ferrite catalyst
[0041] Take 0.8g of ferric oxide and 2.33g of bismuth oxide, put them into a mortar and add anhydrous ethanol for grinding for 0.5 hours to obtain a uniform mixed powder, put it into a nickel crucible, place it in a muffle furnace and roast it at 600°C for 1 hour. After natural cooling, grind it in a mortar to obtain bismuth ferrite catalyst BFO (pure), and its XRD pattern is shown in Figure 4 From the figure (pure), we can see that 24.70°, 27.68°, 30.29°, 32.98°, 53.99°, 55.61° and 61.76° correspond to the (220), (310), (222), (321), (600), (611) and (631) planes of BFO, respectively, indicating that pure bismuth silicate Bi 25 FeO 40 Successfully synthesized.
[0042] Comparative Example 3: Preparation of bismuth silicate and bismuth ferrite composite catalyst
[0043] 0.8 g of silicon dioxide, 0.8 g of ferric oxide and 4.66 g of bismuth oxide were put into a mortar and ground with anhydrous ethanol for 0.5 hours to obtain a uniform mixed powder, which was put into a nickel crucible and calcined at 600 ° C in a muffle furnace for 1 hour. After natural cooling, the bismuth silicate and bismuth ferrite composite catalyst BSFO (pure) was obtained by grinding with a mortar. The XRD pattern is shown in Figure 4 , it can be seen from the figure that it also contains Bi 25 FeO 40 and Bi 12 SiO 20 characteristic peaks.
[0044] Comparative Example 4: Preparation of amorphous manganese dioxide catalyst
[0045] Take 0.845g of manganese sulfate monohydrate and dissolve it in 50mL of deionized water, record it as solution A, take 0.527g of potassium permanganate and dissolve it in 50ml of deionized water, record it as solution B, add solution A dropwise into solution B to obtain a uniform mixed solution; put the mixed solution into a constant temperature water bath heating pot, keep it warm at 50℃ for 12h, filter it after cooling naturally, rinse the solid with water 5 times, dry it at 60℃ for 12h, grind it with a mortar to obtain an amorphous manganese dioxide catalyst, the SEM image of the amorphous manganese dioxide catalyst is shown in Figure 5 From the figure, it can be seen that the amorphous manganese dioxide catalyst is hydrangea-shaped, and its XRD pattern is shown in Figure 1 , showing very weak diffraction peaks, indicating the amorphous structure of MnO2.
[0046] Example 6: Application of the catalysts in Examples 1-5 and Comparative Examples 1-4 in treating antibiotic wastewater
[0047] 1. Weigh 40 mg of each of the catalyst carrier BSFO and the catalyst BSFM in Example 1, the bismuth silicate catalyst BSO (pure) in Comparative Example 1, the bismuth ferrite catalyst BFO (pure) in Comparative Example 2, the bismuth silicate and bismuth ferrite composite catalyst BSFO (pure) in Comparative Example 3, and the amorphous manganese dioxide catalyst in Comparative Example 4, respectively, and place them in 40 mL of a tetracycline hydrochloride solution with a concentration of 10 mg / L. After mixing, place them in an ultrasonic instrument or a constant temperature oscillator (with a speed of 120 r / min) for catalytic degradation reaction. Take 3 mL of the tetracycline hydrochloride solution at 15 min, 30 min, 45 min, 60 min, 90 min, and 120 min, respectively, and measure the absorbance of tetracycline hydrochloride in the solution with a spectrophotometer. Calculate the degradation efficiency of the tetracycline hydrochloride solution under different time conditions with different catalysts.
[0048] Results Figure 6 , 7 It can be seen from the figure that the degradation effect of tetracycline hydrochloride under ultrasonic conditions for 120 minutes by different catalysts is better than that under oscillation conditions, and the degradation rate of tetracycline hydrochloride by the catalyst BSFM of Example 1 under ultrasonic conditions is 97.28%; both are higher than the catalyst carrier BSFO and the catalysts of Comparative Examples 1-4, indicating that the catalyst BSFM has efficient piezoelectric catalytic performance and can effectively catalyze the degradation of antibiotics.
[0049] The fitting results of the degradation rate constant are shown in Figure 8. It can be seen from the figure that the degradation rate of tetracycline hydrochloride by catalyst BSFM is several times that of other types of catalysts, indicating that the catalytic performance of catalyst BSFM is excellent.
[0050] 2. Degradation of tetracycline hydrochloride by the catalysts of Examples 2 to 5 under ultrasonic conditions, using the same method as above;
[0051] The degradation rate of tetracycline hydrochloride by the catalyst of Example 2 in 120 min was 87.96%, the degradation rate of tetracycline hydrochloride by the catalyst of Example 3 in 120 min was 87.96%, the degradation rate of tetracycline hydrochloride by the catalyst of Example 4 in 120 min was 92.23%, and the degradation rate of tetracycline hydrochloride by the catalyst of Example 5 in 120 min was 95.58%.
[0052] Example 7: Application of the catalysts in Examples 1 to 5 and Comparative Examples 1 to 4 in treating wastewater containing As(III)
[0053] 1. Weigh 40 mg of each of the catalyst carrier BSFO, the catalyst BSFM, the bismuth silicate catalyst BSO (pure) of Comparative Example 1, the bismuth ferrite catalyst BFO (pure) of Comparative Example 2, the bismuth silicate and bismuth ferrite composite catalyst BSFO (pure) of Comparative Example 3, and the amorphous manganese dioxide catalyst of Comparative Example 4 in Example 1, respectively, and place them in 40 mL of 5 mg / LAs(III) solution at a concentration of 5 mg / LAs(III). After mixing, place them in an ultrasonic instrument or a constant temperature oscillator (at a speed of 120 r / min) for catalytic degradation reaction. Take 5 mL of As(III) solution at 15 min, 30 min, 45 min, 60 min, 90 min, and 120 min, respectively, and detect the concentration of residual As in the solution by inductively coupled plasma mass spectrometry. Calculate the degradation efficiency of As(III) solution by different catalysts under different time conditions.
[0054] Results Fig. 9 , 10 The degradation effect of catalyst BSFM in Example 1 on As(III) is better than that of other catalysts under both ultrasonic and oscillating conditions. The degradation rate of As(III) is 76.52% at 120 min under oscillating conditions and 95.56% at 120 min under ultrasonic conditions. This indicates that catalyst BSFM has efficient piezoelectric catalysis.
[0055] The degradation rate constant fitting results are shown in Fig.11 ,It can be seen from the figure that the rate of catalyst BSFM is dozens of times that of other catalysts, indicating that the catalytic performance of catalyst BSFM is excellent.
[0056] 2. Degradation of As(III) by the catalysts of Examples 2 to 5 under ultrasonic conditions, using the same method as above;
[0057] The degradation rate of As(III) by the catalyst of Example 2 in 120 min was 85.56%, the degradation rate of As(III) by the catalyst of Example 3 in 120 min was 88.95%, the degradation rate of As(III) by the catalyst of Example 4 in 120 min was 90.58%, and the degradation rate of As(III) by the catalyst of Example 5 in 120 min was 92.45%.
Claims
1. A method for preparing a catalyst having piezoelectric properties using copper slag, characterized in that: The dried copper slag is crushed and sieved, and then calcined at 450-550°C. The calcined copper slag is mixed with Bi2O3, and then anhydrous ethanol is added to grind and mix, and then calcined at 550-650°C. The calcined product, manganese sulfate monohydrate and water are mixed, and potassium permanganate solution is added dropwise to the mixture. After mixing, it is heated in a water bath at 45-55°C. The reaction product is separated into solid and liquid, and the solid is washed, dried and ground to obtain a catalyst with piezoelectric properties.
2. The method for preparing a catalyst having piezoelectric properties using copper slag according to claim 1, characterized in that: The mass ratio of roasted copper slag to Bi2O3 is 1:0.3-2.
3. The method for preparing a catalyst having piezoelectric properties using copper slag according to claim 1, characterized in that: The mass ratio of the roasted product to manganese sulfate monohydrate is 1.7-8.5:1, and the mass ratio of the roasted product to potassium permanganate is 2.7-14:
1.
4. Use of the catalyst prepared by the method for preparing a catalyst with piezoelectric properties using copper slag as described in any one of claims 1 to 3 in catalytic degradation of antibiotics and arsenic.
Citation Information
Patent Citations
New application of copper slag-based FeC2O4 / SiO2 composite photocatalyst
CN117563639A
Preparation method and application of copper smelting slag porous geopolymer microsphere photothermal catalyst
CN117680165A
Preparation method and application of Mn-doped copper slag-based geopolymer derived hollow porous microspheres
CN117696067A
